Scientific Substantiation of the Work Shift Structure Correction of Granite Quarry Workers - Oleg Kruzhilko; Natalia Volodchenkova; Oleksii Polukarov (Trends in Ecological and Indoor Environmental Engineering, 2023)
In Ukraine, more than 70 % of mining operations are carried out in quarries. The mining industry has negative impacts on society, especially workers in the industry. The International Labour Organization states that the mining sector is one of the most dangerous sectors in the world. The current study was designed to understand the occupational safety and health situation in the mining industry at the granite quarries in Ukraine, because the exceeding accepted standards for factors of the production environment and labour process contributes to the development of occupational diseases. The study aimed to improve the working conditions of mining workers by adjusting the work shift structure. The main task was to plan an hourly work shift schedule that takes into account the influence of harmful production factors without compromising production efficiency. The study found that the influence of all four factors was reduced to acceptable limits after changing the work shift schedule. For the dust factor, the danger level was reduced from 4 to 1.25, for vibration – from 5.94 to 2.05, for noise – from 91 to 88, for severity of work – from 2.06 to 1.86. The achieved effect is explained by a reduction in the time an employee spends in hazardous conditions. Similar studies should be carried out for each profession in the extractive industry.